PBSC mobilization in lymphoma patients: analysis of risk factors for collection failure and development of a predictive score based on the kinetics of circulating CD34+ cells and WBC after chemotherapy and G‐CSF mobilization. Issue 3 (29th May 2014) - Rossi, Giuseppe; Skert, Cristina; Morello, Enrico; Almici, Camillo; Arcaini, Luca; Basilico, Claudia; Cavalli, Lara; Botto, Barbara; Castelli, Andrea; Pica, Gianmatteo; Ripamonti, Francesco; Salvi, Flavia; et al.
Abstract: Autologous stem cell transplantation (ASCT) is a potentially curative treatment of lymphoma, but peripheral blood stem cell (PBSC) mobilization fails in some patients. PBSC mobilizing agents have recently been proved to improve the PBSC yield after a prior mobilization failure. Predictive parameters of mobilization failure allowing for a preemptive, more cost‐effective use of such agents during the first mobilization attempt are still poorly defined, particularly during mobilization with chemotherapy + granulocyte colony‐stimulating factor (G‐CSF). We performed a retrospective analysis of a series of lymphoma patients who were candidates for ASCT, to identify factors influencing PBSC mobilization outcome. Premobilization parameters—age, histology, disease status, mobilizing protocol, and previous treatments—as well as white blood cell (WBC) and PBSC kinetics, markers potentially able to predict failure during the ongoing mobilization attempt, were analyzed in 415 consecutive mobilization procedures in 388 patients. We used chemotherapy + G‐CSF in 411 (99%) of mobilization attempts and PBSC collection failed (<2 × 10 6 CD34+ PBSC/kg) in 13%. Multivariable analysis showed that only a low CD34+ PBSC count and CD34+ PBSC/WBC ratio, together with the use of nonplatinum‐containing chemotherapy, independently predicted mobilization failure. Using these three parameters, we established a scoring system to predict risk of failure during mobilization ranging from 2 to 90%, thus allowing a selective use of a preemptive mobilization policy. Copyright © 2014 John Wiley & Sons, Ltd.